Psychometric properties of the Zephyr bioharness device: a systematic review - Goris Nazari; Pavlos Bobos; Joy C. MacDermid; Kathryn E. Sinden; Julie Richardson; Ada Tang (BMC, 2018)
Abstract Background Technological development and improvements in Wearable Physiological Monitoring devices, have facilitated the wireless and continuous field-based monitoring/capturing of physiologic measures in healthy, clinical or athletic populations. These devices have many applications for prevention and rehabilitation of musculoskeletal disorders, assuming reliable and valid data is collected. The purpose of this study was to appraise the quality and synthesize findings from published studies on psychometric properties of heart rate measurements taken with the Zephyr Bioharness device. Methods We searched the Embase, Medline, PsycInfo, PuMed and Google Scholar databases to identify articles. Articles were appraised for quality using a structured clinical measurement specific appraisal tool. Two raters evaluated the quality and conducted data extraction. We extracted data on the reliability (intra-class correlation coefficients and standard error of measurement) and validity measures (Pearson/Spearman's correlation coefficients) along with mean differences. Agreement parameters were summarised by the average biases and 95% limits of agreement. Results A total of ten studies were included: quality ratings ranged from 54 to 92%. The intra-class correlation coefficients reported ranged from 0.85-0.98. The construct validity coefficients compared against gold standard calibrations or other commercially used devices, ranged from 0.74-0.99 and 0.67-0.98 respectively. Zephyr Bioharness agreement error ranged from − 4.81 (under-estimation) to 3.00 (over-estimation) beats per minute, with varying 95% limits of agreement, when compared with gold standard measures. Conclusion Good to excellent quality evidence from ten studies suggested that the Zephyr Bioharness device can provide reliable and valid measurements of heart rate across multiple contexts, and that it displayed good agreements vs. gold standard comparators - supporting criterion validity.